Clinicopathological features of the tauopathies. (1st August 2005) - Murray, B.; Lynch, T.; Farrell, M.
Abstract : Developments in molecular neuropathology have led to protein-based classification systems for neurodegenerative disorders. Key proteins include α-synuclein, amyloid and tau. Alternative mRNA splicing and post-translational change, induced by a bewildering variety of protein modifying processes such as phosphorylation and ubiquitination, have generated insights into new mechanisms of selective neuronal degeneration. The task now is to bring these developments in protein chemistry to the clinic, to try to determine whether this biochemical diversity can help in explaining the phenotypic variability that is so typical of neurodegeneration in general. In this review, we will explore the clinicopathological diversity of the tau-related disorders with specific reference to three of the most common tauopathies, frontotemporal dementia (familial and sporadic), progressive supranuclear palsy and corticobasal degeneration.